Compositional Changes in Compost during Composting and Growth of Agaricus bisporus - Iiyama, Kenji (1994)
Samples from conventional compost taken at various stages of composting and mushroom (Agaricus bisporus) growth were analyzed for changes in 80% ethanol and water extracts, monosaccharides in acid hydrolysates of polysaccharides, lignin concentration, and lignin structural features. Variable amounts of extraneous inorganic solids in the form of fine sandy particles were removed by sedimentation of the samples in a carbon tetrachloride-dibromomethane mixture. During composting, about two-thirds of the initial wall polysaccharides were consumed by compost microorganisms, and only 17% of the total polysaccharides were used during mushroom production. The relative lignin content of composts as measured by the acetyl bromide procedure increased, both during composting and mushroom growth, and the chemical structure of lignin was altered by condensation and oxidation reactions.